Overcoming the barriers to learning and participation. Recent acquisitions on inclusive didactic and on the training of the support teacher as an action system: evidences - Isidori, Maria Vittoria (Formazione & insegnamento, 2018)
The present work can be included in the debate about the education sustainability and its aim is to make a contribution to the reflection on the inclusive teachers’ training starting from the outcomes of a survey carried on during the III Cycle of the annual Course of ‘Specialization for teaching support to students with disabilities’ of the University Aquila. These outcomes were also analyzed with reference to the results of another survey driven, adopting the same methodology, in the previous edition (II Cycle) of the above mentioned course. The objective was to investigate (through a pre post course participation detection) the development of international inclusive teaching attitudes with the course attendees. Development common to both the training experiences examined.